YOGHURT DENGAN PENAMBAHAN UBI JALAR UNGU SEBAGAI SNACK UNTUK PENCEGAHAN STUNTING - Fariza Yulia Kartika Sari; Zalfa Iqlima Bilqis; Indanah Indanah (Universitas Muhammadiyah Kudus, 2024)
Stunting is a nutritional problem that is a top priority for the Ministry of Health. This stunting problem has a negative impact, namely increased morbidity and mortality, poor child development, increased risk of infection and decreased productivity which has an impact on decreasing economic capacity. One way to overcome stunting is by providing MP-ASI which is high in antioxidants. Purple sweet potato yogurt is one of Blabla's functional food products. The aim of this research was to determine the nutritional and antioxidant content of purple sweet potato yogurt. This research method uses an experimental design with a completely randomized design (CRD) with one factor, namely the addition of purple sweet potato 35 g, 40 g, 45 g. Purple sweet potato yogurt is explained physically (pH levels and viscosity) and chemically (analysis of nutritional content and antioxidant activity). The data obtained was explained using SPSS 23.0. The research results showed that formula three, namely yogurt with the addition of 45 g of purple sweet potato, had higher levels of air, ash, protein and fat compared to the other formulas. Formula 3 contains the highest antioxidant activity compared to other formulas, namely 38.9%. The conclusion of this research is that the higher the addition of purple sweet potato to yogurt, the higher the antioxidant activity, so that it can be used as an MP-ASI product for stunted children.